2014
DOI: 10.1080/00405000.2014.917812
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and morphology of bead-on-string structures in centrifugal forcespun PA6 fibers

Abstract: This research aimed at investigating the morphology and frequency of bead-on-string occurrences on forcespun nano-and sub-micron fibers. The formation of bead-on-string structures was observed on a range of fiber samples forcespun in varied conditions from PA6 solutions of different concentrations. Bead-on-string structures were characterized for morphology using SEM micrographs, and were counted on all samples. Two major factors appeared to affect both the morphology and the bead count, namely spinning soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Low viscosity of the Solution A may be the causation of the beads on the fibers. It is found that solution with low viscosity encourages the formation of the beads . This is due to the insufficient viscoelastic force to overcome the surface tension of the solution jet from the syringe, favoring the formation of larger beads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low viscosity of the Solution A may be the causation of the beads on the fibers. It is found that solution with low viscosity encourages the formation of the beads . This is due to the insufficient viscoelastic force to overcome the surface tension of the solution jet from the syringe, favoring the formation of larger beads.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer solutions with high viscosity, high surface tension, and low net charge density are prone to the formation of beads on the electrospun fibers. In a more recent study conducted by Krifa et al ., larger needle or spinneret size can also encourage the formation of beads on the spun fibers apart from the viscosity of the polymer solution. In the aspect of the spinning process, Bu et al .…”
Section: Introductionmentioning
confidence: 97%
“…The morphology of forcespun fibers is a function of spinning fluid characteristics, such as solution concentration (in the case of solution spinning) and melt viscosity (for melt spinning), as well as operating parameters that include rotational speed and orifice size of the spinneret, heating temperature, and collection system. 21,[23][24][25][26] Sarkar et al 21 reported that spinneret rotational speed is negatively correlated to fiber diameter in limited spinning tests conducted on poly(ethylene oxide) (PEO). Shanmuganathan et al 23 used a laboratory forcespinning machine to melt-spin poly(butylene terephthalate) nanofibers.…”
mentioning
confidence: 99%
“…Processing parameters that have been shown to affect fibre diameter are the concentration of the polymer solution and needle size [17]. In their study, Krifa et al evaluated the beads on a string phenomenon using PA6 solutions and performed an analysis of variance (ANOVA) to calculate the significance of these variables on the reduction of fibre beading.…”
Section: Introductionmentioning
confidence: 99%